Globalisasi dan Keberagamaan di Asia: Pemikiran Kwok Pui-Lan—Teologi Poskolonial Feminis Asia - Odniel Hakim Gultom (Faculty of Theology Duta Wacana Christian University, 2016)
Abstract The main thesis of this article is to present the phenomenon of globalization about cultural change (and economic) that gives effect to the